Identifying the bank lending channel in Brazil through data frequency - Christiano A. Coelho; Jo\~ao M. P. de Mello; Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
Using the different response timings of credit demand and supply, we isolate supply shifts after monetary policy shocks. We show that the bank lending channel exists in Brazil: after an increase (decrease) in the basic interest rate (Selic), banks reduce (increase) the quantity of new loans and raise (lower) interest rates. However, contrary to the empirical literature for the US, we find evidence that large banks react more than smaller ones to monetary policy shocks. Results may have important implications for monetary policy transmission in light of the recent wave of concentration in the Brazilian banking industry.
Keywords: E52; E58; 330; monetary policy transmission; credit markets; bank lending channel. JEL Code: E52; E58; Kreditmarkt; Kreditgeschäft; Geldpolitik; Geldpolitische Transmission; Brasilien